2011
DOI: 10.1111/j.1365-313x.2011.04705.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix solubilization and cell wall weakening by β‐expansin (group‐1 allergen) from maize pollen

Abstract: SUMMARYBeta-expansins accumulate to high levels in grass pollen, a feature apparently unique to grasses. These proteins, which are major human allergens, facilitate pollen tube penetration of the maize stigma and style (the silk). Here we report that treatment of maize silk cell walls with purified b-expansin from maize pollen led to solubilization of wall matrix polysaccharides, dominated by feruloyated highly substituted glucuronoarabinoxylan (60%) and homogalacturonan (35%). Such action was selective for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 67 publications
3
61
0
1
Order By: Relevance
“…This new information complements previous data showing that EXPB1 specifically loosens grass CWs and solubilizes hsGAX from maize CWs Tabuchi et al, 2011). Previous biochemical data indicate that hsGAX displays only weak binding to cellulose (Carpita, 1983), thus it is unlikely to serve as a load-bearing linker directly interconnecting cellulose microfibrils but may act as space-filling interstitial material between cellulose microfibrils (Carpita et al, 2001).…”
Section: A Model Of Expb1-mediated Cw Looseningsupporting
confidence: 85%
See 3 more Smart Citations
“…This new information complements previous data showing that EXPB1 specifically loosens grass CWs and solubilizes hsGAX from maize CWs Tabuchi et al, 2011). Previous biochemical data indicate that hsGAX displays only weak binding to cellulose (Carpita, 1983), thus it is unlikely to serve as a load-bearing linker directly interconnecting cellulose microfibrils but may act as space-filling interstitial material between cellulose microfibrils (Carpita et al, 2001).…”
Section: A Model Of Expb1-mediated Cw Looseningsupporting
confidence: 85%
“…Consistent with this idea, Tabuchi et al (2011) found that treatment of maize CWs with EXPB1 induces release (solubilization) of a form of GAX with a high degree of arabinose substitution (hsGAX) as well as smaller amounts of homogalacturonan (HG). Extensive testing of EXPB1 did not detect any enzymatic activities, just as tests for enzymatic activities with a-expansins and bacterial expansins proved to be negative (McQueen-Mason and Cosgrove, 1995;Kerff et al, 2008;Georgelis et al, 2011Georgelis et al, , 2015.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…One of the hypothesized actions of expansin is the weakening of noncovalent binding between cellulose fibers, and it is supported by the finding of expansin weakening the hydrogen bonding of pure cellulose paper (McQueen-Mason and Cosgrove, 1994). Meanwhile, many studies have reported that expansins have no hydrolytic or other enzymatic activities (McQueen-Mason et al, 1993;Li and Cosgrove, 2001;Tabuchi et al, 2011). In addition to that, Cosgrove et al (1998) also mentioned that although expansin lacks hydrolytic activity itself, it does enhance the hydrolysis of crystalline cellulose by cellulases.…”
Section: Discussionmentioning
confidence: 97%